The Problems of Budgeting and Financial Decision Process - Vávra, Jan (Ekonomika, 2004)
Many companies recognize that the traditional annual budget (produced near yearend and then used as a guide for the following year even though it is out of date) is just not good enough. Instead, they are turning to alternative budgets (forecasts) that are updated every few months. They impose new requirements on financial decision-making. Management must access and process information more quickly, and this often means a change of the current practice of data collection and processing or even acquiring special software to do the job. The budgeting process and financial decisions can be accelerated and improved in several ways, and the paper deals with advantages and disadvantages of the possible ways.